Dual impact analysis of GSTT1 polymorphisms on the metformin response and cardiovascular risk: A novel integrated approach in type 2 diabetes mellitus management - Dewi, Ni Luh Made Noviana (PT. Mega Science Indonesia, 2025)
Although genetic variations in glutathione S-transferase (GST) have been linked to type 2 diabetes mellitus (T2DM), the relationships among GSTT1 polymorphisms, metformin effectiveness, and cardiovascular risk remain unclear. This study investigated the association between the GSTT1 null genotype and the metformin monotherapy response while simultaneously assessing its impact on atherosclerotic cardiovascular disease risk. This case-control study examined 84 T2DM patients aged 30-70 years, categorized into metformin therapy responders and nonresponders. This study employed multiplex PCR for GSTT1 genotyping and utilized the pooled cohort equation for cardiovascular risk assessment, offering a comprehensive analysis of both genetic and clinical parameters. GSTT1 genetic variations were not significantly associated with metformin response (odds ratio [OR] 1.773, p=0.306) or cardiovascular risk (OR 1.086, 95% CI: 0.46-2.56, p=1.000). The analysis revealed distinct patterns in clinical parameters between the GSTT1 null and wild-type genotypes, particularly in terms of glycemic control indicators and lipid profiles, although these differences did not reach statistical significance. This study presents a novel approach by simultaneously examining both the therapeutic response and cardiovascular risk in relation to GSTT1 polymorphisms, distinguishing it from previous studies that typically focused on either aspect in isolation. These findings suggest that while genetic variations in GSTT1 may influence metabolic parameters, their direct impact on metformin effectiveness and cardiovascular risk may be more complex than previously thought.